Wedding Center Di Surakarta Dengan Mengadopsi Pada Gaya Arsitektur Bangsal Pracimayasa Pura Mangkunegaran - Jatmika, Galuh, Dr. Ir. Dhani Mutiari, MT, Yayi Arsandrie, ST., MT (2015)
Wedding Center in Surakarta by adopting on the architectural style of the ward Pracimayasa Pura Mangkunegaran is a place or building or a container that is used to create a wedding that provides all the amenities and facilities that are in need in deploying weddings located in Surakarta by adopting the style of the architecture of Ward Pracimayasa. Based on problems in the face, leading to the idea or the idea to provide a seat for the completeness of a wedding that can be reached in one place only. The completeness of the form of wedding dresses, wedding decorations, flowers, cake, souvenirs, wedding organizer, consultant, salon, and do not forget also the building as a container holding of the marriage. The concept of a style of architecture adopted the Pracimayasa Ward is one of the few Ward found Pura Mangkunegaran. most of the space in the building Pracimayasa got the influence of European architecture, china, Bali and Java found on the motif accessories and engraving in the space. In line with the ideas and the idea of the author with the passage of time may the Wedding Center in Surakarta by adopting on the architectural style of the Pura Mangkunegaran Pracimayasa Ward could be beneficial for society city of Surakarta.